Mutant Cohesin in Premature Ovarian Failure - Caburet, Sandrine; Arboleda, Valerie A; Llano, Elena; Overbeek, Paul A; Barbero, Jose Luis; Oka, Kazuhiro; Harrison, Wilbur; Vaiman, Daniel; Ben-Neriah, Ziva; García-Tuñón, Ignacio; Fellous, Marc; Pendás, Alberto M; et al. (The New England journal of medicine, 2014)
Few genes have been implicated in sporadic premature ovarian failure. This study implicates STAG3, which encodes a cohesin, a protein that mediates chromosome pairing during meiosis. Premature ovarian failure, the end point of primary ovarian insufficiency, affects approximately 1% of women worldwide. Patients with premature ovarian failure present with at least a 6-month history of amenorrhea and elevated plasma levels of follicle-stimulating hormone (>40 mIU per milliliter). The disorder can result from premature depletion of the follicle pool, follicular atresia, follicle growth arrest, or ovarian dysgenesis. Although a majority of cases are idiopathic, premature ovarian failure can be caused by infectious agents, chemotherapy, pelvic surgery, autoimmune disease, environmental factors, or genetic conditions. 1 The disorder is observed in syndromic diseases — for example, Turner's syndrome and BPES . . .